2003
DOI: 10.1002/ajmg.a.20058
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 40 sporadic or familial neonatal and pediatric cases with severe unexplained respiratory distress: Relationship to SFTPB

Abstract: We have analyzed surfactant protein B (SP-B) and its encoding gene (SFTPB, MIM 178640) in 40 unrelated pediatric patients with unexplained respiratory distress (URD). There was high consanguinity (eight kindreds) and an underlying autosomal recessive trait could be inferred in most cases, with overall high sex ratio (32/17) suggesting proband's gender to impact on penetrance. The clinical/biological presentations fitted into three major nosologic frameworks. I: SP-B deficiency (nine probands), complete or inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 48 publications
2
59
0
Order By: Relevance
“…SP-B, a dimer of 16 kDa, was detected easily in all cases investigated except for the single case of hereditary SP-B deficiency. Together with the finding of lacking SP-B in all other reported cases of this genetic disorder (7,17,18,(24)(25)(26) and the successful rescue of SP-B-deficient knockout mice (27), the analysis of BALF for SP-B concentration appears diagnostically helpful when pediatric DPLD potentially including this rare condition are investigated. In this context, it must be recommended to sample BAL before exogenous surfactant is applied, as the latter usually contains both SP-B and SP-C whose in vivo half-lives may be very long (28)(29)(30).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…SP-B, a dimer of 16 kDa, was detected easily in all cases investigated except for the single case of hereditary SP-B deficiency. Together with the finding of lacking SP-B in all other reported cases of this genetic disorder (7,17,18,(24)(25)(26) and the successful rescue of SP-B-deficient knockout mice (27), the analysis of BALF for SP-B concentration appears diagnostically helpful when pediatric DPLD potentially including this rare condition are investigated. In this context, it must be recommended to sample BAL before exogenous surfactant is applied, as the latter usually contains both SP-B and SP-C whose in vivo half-lives may be very long (28)(29)(30).…”
Section: Discussionmentioning
confidence: 91%
“…In particular, no studies have compared the full range of these diseases, to yield better estimates of variability and to examine the relative importance of biochemical determinations of their BALF levels. It has been shown that the levels of SP-C in patients with known mutations in SFTPB (17,18), SFTPC (19,20), ABCA3 (21), and TTF1 (22) are low. Thus, we hypothesized that SP-C might serve as a helpful screening tool for such and additional surfactant dysfunction disorders.…”
mentioning
confidence: 99%
“…Genetic variation may account for some of the differences but not for all. For example, some patients with Sftpb deficiency or reduced Sftpb levels have no detectable Sftpb mutations in coding and regulatory regions (81). Notably, Sftpb gene expression can be inhibited by decreased binding of Nkx2-1 to the Sftpb promoter without alteration of the nuclear levels of Nkx2-1 protein (11).…”
Section: Discussionmentioning
confidence: 99%
“…As the need for supplementary oxygen increased and chest radiographs showed persistent diffuse bilateral pulmonary infiltrates, the boy was transferred to a university hospital at the age of 11 months. A SFTPB mutation was excluded by SFTPB sequencing [5]. Recently, a neutralising antibody against GM-CSF in adult patients with idiopathic PAP was characterised and it has also been shown that such auto-antibodies are diagnostic for autoimmune (idiopathic) PAP [9,15,16].…”
Section: Study Subjectmentioning
confidence: 99%
“…As an eosinophilic and periodic acid Schiff (PAS)-positive material was found in the alveoli, hereditary SP-B deficiency was initially described as "congenital alveolar proteinosis syndrome" [3,4]. However, in contrast to "cryptogenic" congenital, idiopathic and secondary pulmonary alveolar proteinosis (PAP), hereditary SP-B deficiency is associated with SP-B gene (SFTPB) mutations and is characterised by a complete or incomplete deficiency of SP-B, an aberrant processing of proSP-C and a lack of mature SP-C [5][6][7].…”
mentioning
confidence: 99%